Approaches to Legal Rationality - Gabbay, Dov M.; Canivez, Patrice; Rahman, Shahid; Thiercelin, Alexandre; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Legal theory, political sciences, sociology, philosophy, logic, artificial intelligence: there are many approaches to legal argumentation. Each of them provides specific insights into highly complex phenomena. Different disciplines, but also different traditions in disciplines (e.g. analytical and continental traditions in philosophy) find here a rare occasion to meet. The present book contains contributions, both historical and thematic, from leading researchers in several of the most important approaches to legal rationality. One of the main issues is the relation between logic and law: the way logic is actually used in law, but also the way logic can make law explicit. An outstanding group of philosophers, logicians and jurists try to meet this issue. The book is more than a collection of papers. However different their respective conceptual tools may be, the authors share a common conception: legal argumentation is a specific argumentation context.
Introduction -- Abstracts -- Part I The Specificity of Legal Reasoning -- Part II Legal Reasoning and Public Reason -- Part III Logic and Law -- Part IV New Formal Approaches to Legal Reasoning -- Part V Logic in the Law.
Keywords: Law; Philosophy (General).; Logic; Artificial intelligence; Law; Theories of Law, Philosophy of Law, Legal History; Logic; History of Philosophy; Political Science, general; Artificial Intelligence (incl. Robotics).